2020
DOI: 10.2337/db20-1572-p
|View full text |Cite
|
Sign up to set email alerts
|

1572-P: Neighborhood Investments and Cardiometabolic Health in Two Predominantly African-American Communities: A Natural Experiment Study

Abstract: Background: Neighborhood disadvantage is a robust and independent risk factor for poor cardiometabolic health, however, causal relationships have been difficult to establish. We used a natural experiment design to examine neighborhood investment on cardiometabolic risk factors among a randomly selected cohort of residents from two, low-income, urban, and predominately African American matched neighborhoods. Methods: The sample included 532 participants (80% female; mean age=59 years; mean income… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Since subsidised housing estates in Brazil are commonly located in socially disadvantaged areas, 36 37 39 41 which are a potential predictor of poor diabetes management, 1 2 contextual-level interventions may be warranted. Improvements in cardiometabolic health due to a contextual-level intervention were observed, for example, in the study by Gary-Webb et al , 53 which conducted a natural experiment to analyse the effect of neighbourhood investment on cardiometabolic risk factors among a randomly selected cohort of residents from two low-income and predominantly African-American matched neighbourhoods, in 2016–2018. The authors found that residents from the neighbourhood that received more publicly funded investments (housing and commercial investment) showed improvements in hemoglobin A1c and high-density lipoprotein cholesterol levels compared with residents from the neighbourhood that received less investment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since subsidised housing estates in Brazil are commonly located in socially disadvantaged areas, 36 37 39 41 which are a potential predictor of poor diabetes management, 1 2 contextual-level interventions may be warranted. Improvements in cardiometabolic health due to a contextual-level intervention were observed, for example, in the study by Gary-Webb et al , 53 which conducted a natural experiment to analyse the effect of neighbourhood investment on cardiometabolic risk factors among a randomly selected cohort of residents from two low-income and predominantly African-American matched neighbourhoods, in 2016–2018. The authors found that residents from the neighbourhood that received more publicly funded investments (housing and commercial investment) showed improvements in hemoglobin A1c and high-density lipoprotein cholesterol levels compared with residents from the neighbourhood that received less investment.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that residents from the neighbourhood that received more publicly funded investments (housing and commercial investment) showed improvements in hemoglobin A1c and high-density lipoprotein cholesterol levels compared with residents from the neighbourhood that received less investment. 53 …”
Section: Discussionmentioning
confidence: 99%